Teaching Design Thinking in times of COVID-19 - Victorino, Guilherme (2021)
Victorino, G., Henriques, R., & Bandeira, R. (2021). Teaching Design Thinking in times of COVID-19: an online learning experience. In J. Domenech, P. Merello, & E. D. L. Poza (Eds.), 7th International Conference on Higher Education Advances (HEAd’21) (pp. 263-270). Editorial Universitat Politècnica de València. https://doi.org/10.4995/HEAD21.2021.13621